Electromyographic features of the perineum and pelvic floor in patients with an artificial bladder - R.V. Savchuk; F.I. Kostyev; S.V. Golovko; Y.M. Dekhtiar; K.A. Zalyva (Medičnì Perspektivi, 2021)
Aim – to assess the electromyographic features of the pelvic floor muscles and the sphincter apparatus in patients who underwent radical cystprostatectomy with the formation of an artificial bladder.The main study group consisted of 57 patients with muscle invasive bladder cancer who underwent a standard radical cystprostatectomy with ileocystoplasty. The study of the pelvic floor muscular bioelectric activity with computed electromyography (EMG) of the sphincter apparatus of the pelvic organs was carried out on a 2-channel computer electromyograph "NeuroTrac ™ MyoPlus4". The obtained results of the study of the bioelectric activity of the pelvic floor muscles showed a decrease in the amplitude of contractions in the Work Average mode by 42.1% (p≤0.001) for the perineal electrode, and by 35.7% (p≤0.05) for the rectal electrode, compared with the control group, which indicates a low contractility of the muscular diaphragm of the pelvis and may cause incontinence in patients with an artificial bladder. The average deviation over the entire duration of the session in Work mode in the group of patients with neobladder in channels A and B was 2.3 (p≤0.05) and 1.9 (p≤0.05) times higher, respectively, compared with control group. These data indicate an imbalance in the muscle tone of the pelvic floor in patients after extensive reconstructive intervention on the pelvic organs and can potentiate urodynamic disorders in the study group of patients. The average amplitude (Rest Average) of the activity of biopotentials in the resting state of the pelvic floor muscles along channels A and B is higher by 42.4% and 47.6% (p≤0.05), in comparison with the control group, which indicates insufficient relaxation and rest of striated muscles and sphincter. Despite the change in bioelectric potentials from the rectal electrode in the study group of patients, there were no signs of functional insufficiency of the anal sphincter, in contrast to the severity of urinary incontinence, which correlated and corresponded to the results of bioelectrical changes obtained through channels A and B, up to oscillations and loss of complete control. The EMG analysis of the pelvic floor muscles revealed characteristic changes in the biopotentials of the pelvic sphincters and indicated their relationship with the clinical features of the rehabilitation of this group of patients and the prospect of including the biofeedback method. It is a derivative form of the electromyographic signal in the treatment of incontinence in patients with neobladder.